2014
DOI: 10.3389/fpsyg.2014.01344
|View full text |Cite
|
Sign up to set email alerts
|

Mental workload and driving

Abstract: The aim of this review is to identify the most representative measures of subjective and objective mental workload in driving, and to understand how the subjective and objective levels of mental workload influence the performance as a function of situation complexity and driving experience, i.e., to verify whether the increase of situation complexity and the lack of experience increase the subjective and physiological levels of mental workload and lead to driving performance impairments. This review will be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(111 citation statements)
references
References 71 publications
3
105
0
3
Order By: Relevance
“…By comparing within sessions, dfa2 and RPadet were found significantly different between session 1 and 4, while ShanEn between session 3 and 4. Previous studies [15][16][17], showed that as one task's demand increases, HRV becomes more depressed. Added to this, here we found that also on repetitive tasks, there is a depressed HRV over sessions, which is possibly due to an increase in mental workload.…”
Section: Iiiresults and Discussionmentioning
confidence: 99%
“…By comparing within sessions, dfa2 and RPadet were found significantly different between session 1 and 4, while ShanEn between session 3 and 4. Previous studies [15][16][17], showed that as one task's demand increases, HRV becomes more depressed. Added to this, here we found that also on repetitive tasks, there is a depressed HRV over sessions, which is possibly due to an increase in mental workload.…”
Section: Iiiresults and Discussionmentioning
confidence: 99%
“…For instance, Kontogiannis found that behaviors on the road significantly predict traffic accidents in professional drivers [14,59]. Taking into account that the safe operation of motor vehicles depends on a combination of psychomotor skills and environmental factors, variables such as work stressors [58,60,61], cognitive overstimulation [55], weather, road conditions [62], driving performance [51,33], and prolonged interaction with other road users [63] are key factors to consider in the management of safety issues in the transport industry [6].…”
Section: Road Accidentsmentioning
confidence: 99%
“…Finally, the driving task used in this study was relatively simple, and consisted of a rural, straightroad with only one additional vehicle. Such a driving condition could be considered as placing a low mental workload on the driver (Paxion et al, 2014). Hence replicating the study with different driving scenarios with a range of imposed mental workloads would allow for a higher generalisation of the results.…”
Section: Limitations Of the Studymentioning
confidence: 99%